Swot analysis of simulation methods and visualisation of airflow in subsonic wind tunnels - Eliza-Ioana Apostol; Aurel Mihail Țîțu (Journal of Research and Innovation for Sustainable Society)
This paper contains concrete aspects aimed at strengthening research and innovation through specific activities in the field of aerospace research. This involves continuous research, finding new, modern, innovative solutions/processes that satisfy potential customers and through which we can keep competitive with existing aerospace research institutes on the market. In the case of improving the methods of simulation and visualisation of airflow around symmetrical airfoils we have carried out a SWOT analysis because it is a strategic method used to assess internal and external factors that can influence the success of an initiative or strategy.